2021
DOI: 10.1519/jsc.0000000000002742
|View full text |Cite
|
Sign up to set email alerts
|

Jump Training in Rugby Union Players: Barbell or Hexagonal Bar?

Abstract: Weakley, JJS, Till, K, Read, DB, Leduc, C, Roe, GAB, Phibbs, PJ, Darrall-Jones, J, and Jones, B. Jump training in rugby union players: barbell or hexagonal bar?. J Strength Cond Res XX(X): 000-000, 2018-The countermovement jump (CMJ) is an exercise that can develop athletic performance. Using the conventional barbell (BAR) and hexagonal barbell (HEX) while jumping, the intensity can be increased. However, the bar that provides greater adaptations is unknown. Therefore, this study aimed to assess changes in loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Furthermore, a number of these studies have been done within a Smith machine which is expected to increase the reliability of the outputs. However, strength and conditioning practitioners often utilise a wide range of exercises and these are often done with free weights [73][74][75][76]. Additionally,…”
Section: Reliabilitymentioning
confidence: 99%
“…Furthermore, a number of these studies have been done within a Smith machine which is expected to increase the reliability of the outputs. However, strength and conditioning practitioners often utilise a wide range of exercises and these are often done with free weights [73][74][75][76]. Additionally,…”
Section: Reliabilitymentioning
confidence: 99%
“…Table 1 outlines the strength and conditioning training protocols that all subjects undertook across the four-week mesocycle. The resistance training exercises and sessions prescribed were part of the regular preseason routine and were based upon previous research 8,21 . There were two different training routines (session one and session two) and these were completed in an alternating order so that each individual session was completed six times.…”
Section: Rm Strength Assessmentmentioning
confidence: 99%
“…This suggests that by utilizing VLTs, practitioners can prescribe each individual athlete a similar training stimulus irrespective of recent training history. This is made possible by emphasizing the external stimulus (i.e., force, power, and velocity), rather than set and repetition schemes that do not account for athlete differences [ 33 , 34 , 35 ] and have been shown to cause divergent adaptations despite homogenous groups of athletes [ 36 ]. This supports previous work from Weakley et al that demonstrated that VLTs control for differences (e.g., strength and muscular endurance) between participants and allow for homogenous training outputs within training sessions [ 11 ].…”
Section: Discussionmentioning
confidence: 99%